Relax Your Mine : Efektivitas Pelatihan Mindfulness terhadap Pengurangan Tingkat Stress Akademik pada Mahasiswa - Tiara Tri Ariani; Muhammad Iqbal Firmansyah; Syntia Rahma Dini; Tuti Rahmi; Utari Febriani (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
This study aims to determine the effectiveness of mindfulness training in reducing academic stress levels in college students. The background of this study is based on the high academic pressure experienced by college students, which can impact mental health, learning motivation, and academic achievement. Mindfulness was chosen as an intervention because this approach focuses on increasing full awareness of the present moment in a non-judgmental manner, which is believed to help individuals manage stress more adaptively. The study population was college students, with a sample of 15 participants selected using a simple random sampling technique. The study was conducted in a psychology laboratory under controlled conditions to minimize confounding factors. The research approach used was quantitative with an experimental design. The academic stress measurement instrument consisted of 31 items compiled based on the theory of Sarafino and Smith, which has been tested for validity and reliability. The research procedure included measuring academic stress levels before and after mindfulness training. Data analysis was carried out using a t-test to examine differences in pre-test and post-test scores, and a correlation test to examine the relationship between mindfulness application and stress reduction. The results showed a significance value of 0.00 (p < 0.05) and a correlation value of 0.991, which means Ha was accepted. These findings indicate a very strong positive relationship between mindfulness training and reduced academic stress levels. Therefore, it can be concluded that mindfulness training is effective in reducing academic stress in college students. The implication of this study is the need for higher education institutions to consider mindfulness training programs as a preventive and curative intervention strategy to maintain student mental health, enabling them to face academic demands more healthily and productively.